Mempertimbangkan Pengunaan Dabt Asia-Anatolia pada Mushaf Al-Ummah terhadap Mushaf Standar Indonesia dan Mushaf Pakistan - Madzkur, Zaenal Arifin; Nurdin, Ali; Anas, Muhammad Azwar; Mundzir, Muhammad (SUHUF, 2024)
This article examines the use of dabt Asia-Anatolia in the Mushaf al-Ummah by comparing it with the Indonesian Standard Mushaf and the Pakistani Mushaf. The adoption of dabt Asia-Anatolia as an alternative regional system—similar to the al-Masyariqah and al-Magaribah—to accommodate both the Indonesian Standard Mushaf and the Pakistani Mushaf proves to be highly impractical. Through comparative and consistency-based methods, it has been demonstrated that the dabt Asia-Anatolia in the Mushaf al-Ummah still contains numerous inconsistent diacritical markings and tends to intermingle with the dabt al-Masyariqah. This contrasts with the Indonesian Standard Mushaf and the Pakistani Mushaf, which have established consistent diacritical systems and have maintained broader readability and independence for decades. Consequently, efforts to unify the Indonesian Standard Mushaf and the Pakistani Mushaf under the Mushaf al-Ummah framework are deemed ineffective. Instead, it is recommended that the Mushaf al-Ummah develop distinct variants, namely the Mushaf al-Indunisiy, Mushaf al-Ummah al-Pakistaniy, and Mushaf al-Ummah at-Turkiy, to accommodate the specific needs of each region independently.